Defaulting rate and associated factors among patients attending methadone maintenance clinics in Nairobi City County, Kenya - Owuor, Sharon Akoth; Mwanzo, Isaac J. M.; Orago, Alloys S. S. (International Journal Of Community Medicine And Public Health, 2024)
Background: Defaulting from MMT clinics is a major public health problem affecting people globally resulting in high transmission of HIV, hepatitis B and C, increased crime rate, and reduced productivity of an individual. However, defaulting rate in the MMT clinics in Nairobi City County in Kenya remains understudied. This study was aimed at determining the defaulting rate and its associated factors from MMT clinics in Nairobi City County, Kenya. Methods: A cross-sectional analytical study design was employed. Simple random sampling, purposive sampling and stratified sampling were utilized in this study. A sample size of 388 patients was randomly selected. A semi-structured questionnaire was used for data collection. SPSS V.24 was used for data analysis. Results: A response rate of 95% (369) was achieved. Most were youths aged 18-35yrs (60.7%, n=224), male (76.4%, n=282), married (39%, n=144), Christians (51.8%, n=191). The defaulting rate was 53% with marital status, religion, education level, and income source being significantly associated with defaulting (p<0.05). Conclusions: The defaulting rate from MMT was relatively high in Nairobi City County. Defaulting was linked to education, cocaine use before MMT and concurrent drug use during treatment. A number of interventional strategies were proposed by this study to improve MMT programming.